FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ummul Khair; Anwar Junaidi; Tri Yuliana (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2022)
Many factors influence stock prices. One of them is seen from the financial ratios. Currently, banking stocks are experiencing problems due to the coronavirus (COVID-19) outbreak and geopolitical tracing between Turkey and Russia has triggered the index decline. Several banks' share prices experienced a very large decline. Stock prices, stock market closings during the observation period and their movements are always observed by investors. The formulation of the problem in this study is whether Earning Per Share (EPS), Net Profit Margin (NPM), Return on Asset (ROA), and Return on Equity (ROE) have an effect on stock prices. This research was conducted with the aim of knowing the influence of these factors on the stock price of banking companies listed on the Indonesia Stock Exchange. This research uses quantitative methods. The population sample used in this study were banking companies listed on the IDX during the 2016 - 2018 period which included 44 companies and a total sample of 28 companies selected using the purposive sampling method. The results of this study indicate that partially, share prices in banking companies on the IDX during the 2016 - 2018 period rely on Earning Per Share (EPS). Meanwhile, Net Profit Margin (NPM), Return on Asset (ROA), and Return on Equity (ROE) have no effect on stock prices. However, simultaneously Earning Per Share (EPS), Net Profit Margin (NPM), Return on Asset (ROA), and Return on Equity (ROE) have an effect on stock prices.